Cost Control and Financial Performance: An Empirical Investigation of Selected Quoted Manufacturing Firms in Nigeria - Oluwayemisi, Ali-Momoh Betty; Elkanah, Egbekun; Ademola, Omoolorun; Omole Olusola, Mathew; Ishola Mamidu, Aruna (The Journal of Accounting and Management, 2022)
The study examined the link between cost control and the financial performance of selected Nigerian manufacturing firms. Specifically, the study examined the effect of administrative cost, selling and distribution cost on profit after tax of manufacturing firms in Nigeria. The study employed secondary source of data and that were collated through annually financial reports of ten (10) sampled firms through 2011 to 2020. Data were analyzed using descriptive statistics, correlation analysis and panel regression which involve, pooled OLS, random effect estimation and fixed effect estimation including Hausman test as well as post estimation test for the models considered in the study. The findings of the study reported that administrative cost exert insignificant negative effect on profit after tax of the sampled firms, while selling and distribution cost exert insignificant positive effect on profit after tax. Therefore, this study concluded that cost control has both positive and negative effect on financial performance of manufacturing firm in Nigeria, especially, when measured in terms of profit after tax. The study recommended that manufacturing firms need to ensure optimal control of administrative cost as any attempt to employ as positive change agent for a specific financial performance measure can lead to unfavourable effect in another measure. As such control of administrative cost by manufacturing firms should be carried out by taken into consideration the overall performance objective of the firms per time, so that provision can be made available for possible trigger of one measure of financial performance at the expense of the other.